2021
DOI: 10.22492/ije.9.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Machine Translation in the Language Classroom: Turkish EFL Learners’ and Instructors’ Perceptions and Use

Abstract: Online machine translation (OMT) tools are not exclusively designed for language learners; however, these tools are popular among them. This quantitative study investigated the perceptions and attitudes of Turkish speaking EFL learners and instructors in a university English program regarding the use of OMT tools. Two online questionnaires were administered to 462 Turkish-speaking learners and 34 instructors. The results revealed that 94% of the learner participants reported using OMT tools for their language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Additionally, it was discovered in cognitive attitude that students' attitudes toward the use of GT are ethically acceptable regardless of how it is utilized due to the fact that GT aids in language learning and is a translation tool. Similar results were also found in studies by (Mulyani and Afina, 2021;Ata and Debreli, 2021) state that students using GT without permission from their teachers is unacceptable. Meanwhile, students' attitudes toward the use of GT are viewed as cheating depending on how it is used, as GT is viewed as cheating when used for graded assignments and tests.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, it was discovered in cognitive attitude that students' attitudes toward the use of GT are ethically acceptable regardless of how it is utilized due to the fact that GT aids in language learning and is a translation tool. Similar results were also found in studies by (Mulyani and Afina, 2021;Ata and Debreli, 2021) state that students using GT without permission from their teachers is unacceptable. Meanwhile, students' attitudes toward the use of GT are viewed as cheating depending on how it is used, as GT is viewed as cheating when used for graded assignments and tests.…”
Section: Discussionsupporting
confidence: 87%
“…According to unstructured discussion among the lecturers of the Critical Writing course at the University of Bengkulu, using online translation sites can be considered 'cheating', much in the same way as math students derive answers to difficult problems via pre-programmed functions on a calculator. This lecturers' view is in line with the results of the studies regarding this matter, although there were not many of them, that had been done by Mulyani and Afina (2021) and Ata and Debreli (2021). In addition, the lecturers are able to easily distinguish between the student's own writing style and that of the internet, especially when they suddenly "switch" in writing quality and use more sophisticated vocabulary.…”
Section: Introductionsupporting
confidence: 76%
“…Meanwhile, 48% believed sentence translations to be effective or extremely effective, while only 24% stated they were ineffective. About 36% and 24% of participants stated that the OMT was a successful method for translating paragraphs and entire texts (Ata & Debreli, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from research by Ata and Debreli (2021) found that a substantial proportion of language learners used MT tools for reading and writing assignments. However, the promise of MT for language learning cannot be generalised to all language learners as a study on using MT as a CALL tool for language learners at varying levels of proficiency conducted by Garcia and Pena (2011) suggested that MT can be proven to be of substantial help to mostly the beginner and intermediate language learners (lower proficiency).…”
Section: The Mainstreaming Of Computer-mediatedmentioning
confidence: 99%